Evaluation of Conditioning Temperature and Die Specifications on Nursery Pig Performance - M. B. Braun; K. M. Dunmire; C. E. Evans; C. R. Stark; J. C. Woodworth; C. B. Paulk (Kansas Agricultural Experiment Station Research Reports, 2020)
The objective of this study was to determine the effects on growth performance in nursery pigs that is linked to the conditioning temperature and die specifications used during the feed pelleting process. A total of 315 barrows (DNA; 200 × 400; initial BW 13.2 lb) were used in a 35-d growth trial. Upon arrival, pigs were weighed and assigned to pens in a completely randomized design with 5 pigs per pen, and each pen was randomly assigned to 1 of 7 dietary treatments with 9 replications per treatment. Treatments consisted of a mash control (MC) and 6 pelleted diets manufactured using 2 different pellet dies (length/diameter [L:D]: 6.7 and 2.7) and 3 different conditioning temperatures (low, medium, high). Conditioning temperatures for Phase 1 diets pelleted using the 6.7 L:D die were 80, 100, and 120°F and for the die with a L:D 2.7 were 100, 120, and 140°F for the low, medium, and high, respectively. Phase 2 conditioning temperatures for diets pelleted using the die with a L:D of 6.7 were approximately 120, 140, and 160°F and for the 2.7 L:D die were 140, 160, and 180°F for the low, medium, and high, respectively. Diets were fed in three phases as follows, Phase 1: d 0 to 10, Phase 2: d 10 to 25, and Phase 3: d 25 to 35. During Phase 3 all pigs were fed a common mash diet. Overall from d 0 to 35, similar ADG was observed for pigs fed the MC or pelleted diets with the exception of the diet pelleted at the low conditioning temperature using the 6.7 L:D die, which had decreased (P<0.05) ADG compared to MC. When pelleting diets using the 2.7 L:D die, there was a tendency for increased (quadratic,P= 0.077) ADG in pigs fed diets conditioned at increasing temperatures, with the medium temperature having the greatest ADG. There was a tendency for increased (P = 0.088) ADG in pigs fed diets pelleted using the 2.7 L:D die compared to the 6.7 L:D die. Pigs fed pelleted diets, with the exception of the medium temperature on the 2.7 L:D die, had decreased (P<0.05) ADFI compared to the MC. However, diets pelleted using the 6.7 L:D die as well as the diet manufactured at the medium conditioning temperature on the 2.7 L:D die had improved (P<0.05) F/G compared to the MC diet. Additionally, pigs fed diets manufactured using the 6.7 L:D die had decreased (P= 0.030) ADFI compared to those fed diets pelleted using the 2.7 L:D die. In summary, pelleted diets showed poorer ADG but decreased ADFI and improved F/G, and no differences in final BW compared to the MC. Additionally, there was a numerical decrease in pellet quality when treatments were manufactured on the 2.7 L:D die; however, these differences did not result in a growth performance response due to conditioning temperature or die. Overall increasing conditioning temperature decreased the available lysine, and pigs fed pelleted diets had poorer ADG but decreased ADFI and improved F/G compared to those fed the MC.
Keywords: nursery pigs; pellet; pellet die thickness; conditioning temperature